Trends in Portuguese Adolescents Sexual Behavior from 2002 to 2014: HBSC Portuguese Study - Reis,Marta (2018)
This study examined trends in adolescent sexual behaviors from 2002 to 2014 in Portugal. Data were collected using self-reported questionnaires from 8th and 10th graders in classrooms during 2002, 2006, 2010, and 2014. Overall, the prevalence of sexual intercourse, age of sexual initiation, pill use, and sexual intercourse under the influence of alcohol or drugs decreased in Portugal between 2002 and 2014, while condom use increased. Boys and 10th graders more frequently reported having ever had sexual intercourse, boys and 8th graders more frequently reported having had sexual intercourse under the influence of alcohol or drugs, girls and 10th graders more frequently reported having had their first sexual intercourse at 14 years or older (except in 2014, where boys and girls reported more frequently having initiated at 1213 years), and girls and 10th graders reported more frequently having used condoms and the pill (except in 2014) at the last sexual intercourse. Eighth graders more frequently reported having had their first sexual experience at 1213 years (except in 2006).